VERNACULAR ARCHITECTURE IN AFRICA: TOWARDS A NEW PRODUCTION OF PUBLIC FACILITIES - (:unkn) unknown (My University, 2024)
In recent decades, the number of projects for the construction of public facilities promoted by both governments and local or foreign organizations has increased significantly in various African countries. More and more of these projects adopt designs that follow the principles of sustainable development and rely on references from vernacular architecture to meet more adequately with the desired impacts of local development. In order to understand these impact phenomena, a doctoral thesis is currently in progress, exploring various projects that mainly use earth based materials and are located in sub-Saharan Africa, in order to identify the principles of vernacular architecture and its production that should influence the architectural design of a collective facility aiming also to improve housing. In this methodological context, this article details one of the cases analyzed in Benin, entitled "Program for the valorization of the construction sector with local materials". To develop this research, case study and action research methods were mobilized. This study reveals that the use of vernacular design principles is rather common in the production of public facilities, mainly when located in rural areas.
Keywords: African Research